The Impact of Customer Service Quality and Company Image on Customer Loyalty through Satisfaction at PT. Bank Rakyat Indonesia, Enrekang Branch - Rasmani, Dilvia; Rosanti, Novita; Nurdin, Maryam (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
The purpose of this study is to analyze the influence of customer service quality on customer loyalty, to analyze the influence of company image on customer loyalty, to analyze the influence of customer service quality on customer satisfaction, to analyze the influence of company image on customer satisfaction, to analyze the influence of customer satisfaction on customer loyalty, and to analyze the influence of customer service quality on customer loyalty through customer satisfaction and to determine and analyze the influence of company image on customer loyalty through customer satisfaction at PT. Bank Rakyat Indonesia, Enrekang Branch, Kalosi Unit. The analysis method used is the SEM-PLS method with the help of WarpPLS 7.0 for Windows software to test the influence of customer service quality and company image variables both directly and indirectly (through customer satisfaction variables) on customer loyalty variables. The results of this study indicate that the quality of customer service has a positive and significant effect on customer loyalty, the image of the company has a positive and significant effect on customer loyalty, the quality of customer service has a positive and significant effect on customer satisfaction, the image of the company has a positive and significant effect on satisfaction, customer satisfaction has a positive and significant effect on customer loyalty and the quality of customer service has an effect on customer loyalty through customer satisfaction while the image of the company has an effect on customer loyalty through customer satisfaction PT. Bank Rakyat Indonesia, Enrekang Branch, Kalosi Unit.